Al Murunah Webinar on High-Resolution Climate Change Downscaling for Resilient Nature-Based Water Solutions in the MENA Region - Abeyrathna, Wasudha Prabodhani; Fragaszy, Stephen; Samarasekara, Vidhisha (International Water Management Institute, 2025)
The Al Murunah project seeks to improve water security in Egypt, Jordan, Lebanon, and the Occupied Palestinian Territories (OPT) by integrating nature-based solutions for water and agricultural water management strategies (Resilient Nature-Based Water Solutions, RNBWS). The “High-Resolution Climate Change Downscaling for Resilient Nature-Based Water Solutions in the MENA Region” webinar showcased the Al Murunah Project’s groundbreaking findings and insights that can shape the future of sustainable water management in the region.